2015
DOI: 10.1371/journal.pone.0144902
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Shifts in Bacterial Diversity in a Reef Coral

Abstract: This study investigated the relationship between microbial communities in differently sized colonies of the massive coral Coelastrea aspera at Phuket, Thailand where colony size could be used as a proxy for age. Results indicated significant differences between the bacterial diversity (ANOSIM, R = 0.76, p = 0.001) of differently sized colonies from the same intertidal reef habitat. Juvenile and small colonies (<6cm mean diam) harboured a lower bacterial richness than medium (~10cm mean diam) and large colonies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 68 publications
2
70
1
Order By: Relevance
“…Such exposure causes severe oxidative damage within coral tissues during extreme low tides (Brown et al 2002). In recent work, we have also highlighted age-related changes in the microbiome of C. aspera, with the highest microbial diversity in 4-to 12-yr-old corals (Williams et al 2015). Here we describe the community responses of the coral microbiome in two age classes (4-yr-old and 10-yrold colonies) over a 4-d spring-tide sequence.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…Such exposure causes severe oxidative damage within coral tissues during extreme low tides (Brown et al 2002). In recent work, we have also highlighted age-related changes in the microbiome of C. aspera, with the highest microbial diversity in 4-to 12-yr-old corals (Williams et al 2015). Here we describe the community responses of the coral microbiome in two age classes (4-yr-old and 10-yrold colonies) over a 4-d spring-tide sequence.…”
Section: Introductionmentioning
confidence: 87%
“…The large tidal range ([3 m) means that during spring tides, waters leave the reef flat very rapidly (within 20 min), and during the dry season salinity effects induced by the tidal regime are therefore negligible, with the salinity of surface waters varying between 31 and 34% (Charuchinda and Hylleberg 1984). Two age classes of C. aspera (as outlined in Williams et al 2015) were identified on the reef flat to compare microbial communities throughout a tidal cycle in March 2014. Colony ages were determined through alizarin staining, skeleton chronology and by following the demography of this coral population from their initial settlement in the early 1990s (Brown et al 2014;Williams et al 2015).…”
Section: Field Site and Sampling Regimementioning
confidence: 99%
See 3 more Smart Citations